Effects Of Metacognitive Instruction on Listening Comprehension Development In Efl a2 Learners of An Ecuadorian Public University - Espol (2017)
This action research study investigates the effects of metacognitive listening strategy instruction on a2 efl learners’ listening comprehension development of an ecuadorian public university. participants chosen from a purposeful sample (n=100) came from four a2 classes (“basic b courses”) taught by both researchers. The experimental group (n=45) listened to four texts using a metacognitive strategy instruction (planning, evaluation, problem-solving, directed attention, person knowledge, translation). The control group (n=55) listened to the same texts without the application of a metacognitive listening strategy instruction. the study lasted four weeks (2 hours a week of instruction). Quantitative and qualitative data were collected through the use of a preand post-listening tests, metacognitive awareness listening questionnaire (malq), and personal interviews. The purpose of this study is to verify if after this instruction